On Analytic-Synthetic Distinction. A Response from John R. Searle - González Osorio, Álvaro (Disertaciones, 2017)
In his writing "Two dogmas of empiricism", Quine introduces one of the most disputed ideas in contemporary philosophy; this is evidenced by the large number of articles that were generated since its publication. One of the main issues is that there is a distinction between statements analytic and synthetic statements. This article seeks to expose different ideas of Quine in that letter, supplemented, in turn, with his controversial argument of the "Indeterminacy of radical translation" and introduce one of the answers or objections to these points of view pointing to places in which such ideas of Quine seem to shake enough to collapse.
Keywords: Analiticity; Synonim; Meaning; Analityc; Sintetic; Extentional; Intentional